The Effect of Climate Change Literacy on Pro-Environmental Behavior Intention of Teachers - Syaifudin Syaifudin; Agung Purwanto; Budiaman Budiaman (Journal La Edusci, 2026)
Climate change poses significant environmental and social risks, particularly in developing countries such as Indonesia. Education plays a strategic role in strengthening climate awareness and encouraging pro-environmental behavior, with teachers serving as key agents in shaping students’ knowledge, attitudes, and daily practices. This study examined the relationship between climate change literacy and pro-environmental behavior intention among teachers at the Al-Ashriyyah Nurul Iman Islamic Boarding School Foundation in Bogor. A quantitative cross-sectional survey design was employed involving 120 active teachers from elementary, junior high, and senior high school levels. Climate change literacy was measured through three dimensions: knowledge of causes, knowledge of impacts, and knowledge of actions/mitigation, while pro-environmental behavior intention was measured through items related to energy saving, water conservation, waste management, paper reduction, and recycling practices. Data were analyzed using descriptive statistics, Pearson correlation, and multiple linear regression. The findings show that teachers demonstrated stronger agreement with direct causes of climate change, locally perceived impacts, and low-cost mitigation actions. Correlation analysis indicated that all dimensions of climate change literacy were positively associated with pro-environmental behavior intention, with knowledge of actions/mitigation showing the strongest relationship, followed by knowledge of impacts and knowledge of causes. Regression analysis further showed that knowledge of actions/mitigation and knowledge of impacts significantly predicted pro-environmental behavior intention, while knowledge of causes was not a significant predictor when the other dimensions were included in the model. These findings suggest that climate change education for teachers should move beyond scientific explanations of causes and emphasize contextual impacts and applicable mitigation practices.